2023
DOI: 10.1021/acs.jpclett.3c02614
|View full text |Cite
|
Sign up to set email alerts
|

Halide Ions Regulating the Morphologies of PbS and Au@PbS Core–Shell Nanocrystals: Synthesis, Self-Assembly, and Electrical Transport Properties

Feiyue Ge,
Yingying Han,
Changsheng Feng
et al.

Abstract: The geometry and surface state of nanocrystals (NCs) strongly affect their physiochemical properties, self-assembly behaviors, and potential applications, but there is still a lack of a facile method to regulate the exposed facets of the NCs, especially metal@semiconductor core–shell NCs. Herein, we present a reproducible approach for tuning the morphology of PbS NCs from nanocubes to nano-octahedrons by introducing lead halides as precursors. Excitingly, the method can be easily extended to the synthesis of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…PbS and Au@PbS core–shell NCs with different exposed facets were synthesized according to our recent report …”
Section: Experimental Methodsmentioning
confidence: 99%
“…PbS and Au@PbS core–shell NCs with different exposed facets were synthesized according to our recent report …”
Section: Experimental Methodsmentioning
confidence: 99%
“…Organic semiconductors, quantum dot (QD) solids, and other partly ordered condensed matter systems are actively studied as promising materials for solar energy, light-emitting, and other optoelectronic devices. Transport of both charge and excitation has a large effect on the performance of such devices. Despite the differences in chemical composition, it has been shown that, from the point of view of transport, disordered organic semiconductors and QD solids have much in common: energetic disorder can lead to localization of electron and hole states and, consequently, to the hopping transport mechanism. , It is known that spatial-energy correlations significantly affect transport in organic semiconductors, especially materials composed of molecules with large dipole moments, when the correlations are the most long-range (dipole glasses). , Typically, hopping transport in materials with correlated disorder is modeled by numerical Monte Carlo (MC) methods, , but recently an analytic approach has been developed .…”
mentioning
confidence: 99%
“…Organic semiconductors, quantum dot (QD) solids, and other partly ordered condensed matter systems are actively studied as promising materials for solar energy, light-emitting, and other optoelectronic devices. 1 5 Transport of both charge and excitation has a large effect on the performance of such devices. Despite the differences in chemical composition, it has been shown that, from the point of view of transport, disordered organic semiconductors and QD solids have much in common: energetic disorder can lead to localization of electron and hole states and, consequently, to the hopping transport mechanism.…”
mentioning
confidence: 99%